Lebensschutz für den Embryo in vitro - Şentürk Tur, Melike (Schriften zum Strafrecht (SR), 2021)
»Protecting the Life of the Embryo In Vitro« This book explores the question of when exactly human life begins and benefits from protection of life. To address the issue of protection of human life, the hotly debated question of the legal status of the embryo is examined. This research concludes that because The Embryo Protection Act has many gaps and confusions, and in some places has failed to catch up with the new medical advances, it is necessary to make a comprehensive and precise reproductive medicine law.